A Review of Upcycle Coffee Cherry Husk (Cascara) in Kombucha Fermentation: Enhancing Bioactive Compound Potential - Helga Zefanya Wical; Clarinda Djuali; Lamsihar Alex Siregar (JFCN: Journal of Food, Culinary, and Nutrition, 2025)
The growing concern about managing diabetes and adhering to dietary restrictions has led to the development  of  low-sugar,  nutritious  products.  Kombucha,  a  fermented  tea  produced  with  a symbiotic culture of bacteria and yeast (SCOBY), provides essential probiotics and enzymes that aid digestion and boost the immune system. Cascara, or the dried husk of the coffee cherry, contains bioactive compounds such as  quercetin, chlorogenic acid, and  ferulic acid, making it valuable for managing  oxidative  stress,  diabetes,  and  regulating  enzymes.  Combining  cascara  with  kombucha presents an opportunity to enhance the beverage's health benefits. Generally, fermentation for 10– 14  days  with  100  g/L  sucrose  produced  an  optimal  balance  in  pH,  total  phenolic  content  (TPC), flavonoid  content  (TFC),  and  antioxidant  activity.  Cascara  kombucha  also  demonstrated antibacterial effects  against  Staphylococcus aureus,  Escherichia coli, and  Salmonella enterica. This review  highlights  that  cascara  kombucha  is  not  only  a  promising  functional  beverage  but  also  a sustainable strategy for reducing coffee waste and improving post-harvest economic value.